Answer:
![\%Percent = 30 \%](https://tex.z-dn.net/?f=%5C%25Percent%20%3D%2030%20%5C%25)
Step-by-step explanation:
Given
![Shaded = 6\ cubes](https://tex.z-dn.net/?f=Shaded%20%3D%206%5C%20cubes)
![Box = 5\ x\ 4](https://tex.z-dn.net/?f=Box%20%3D%205%5C%20x%5C%204)
Required
Determine the percentage of the shaded cubes
First, we calculate the number of boxes:
![Box = 5\ x\ 4](https://tex.z-dn.net/?f=Box%20%3D%205%5C%20x%5C%204)
Express as multiplication
![Box = 5\ *\ 4](https://tex.z-dn.net/?f=Box%20%3D%205%5C%20%2A%5C%204)
![Box = 20](https://tex.z-dn.net/?f=Box%20%3D%2020)
This implies that there are 20 cubes in the box.
The percentage of the shaded cubes is:
![\%Percent = \frac{Shaded}{Box} * 100\%](https://tex.z-dn.net/?f=%5C%25Percent%20%3D%20%5Cfrac%7BShaded%7D%7BBox%7D%20%2A%20100%5C%25)
![\%Percent = \frac{6}{20} * 100\%](https://tex.z-dn.net/?f=%5C%25Percent%20%3D%20%5Cfrac%7B6%7D%7B20%7D%20%2A%20100%5C%25)
![\%Percent = \frac{6* 100}{20} \%](https://tex.z-dn.net/?f=%5C%25Percent%20%3D%20%5Cfrac%7B6%2A%20100%7D%7B20%7D%20%5C%25)
![\%Percent = \frac{600}{20} \%](https://tex.z-dn.net/?f=%5C%25Percent%20%3D%20%5Cfrac%7B600%7D%7B20%7D%20%5C%25)
![\%Percent = 30 \%](https://tex.z-dn.net/?f=%5C%25Percent%20%3D%2030%20%5C%25)
<em>30% were shaded</em>
Answer:
240 cents
Step-by-step explanation:
Given that,
cost of one lollipop = 65 cents
total amount Josie need to paid = 65 * 4 cents = 260 cents
amount Josie gave = $5
As we know
$1 = 100 cents
$5 = 100 * 5 cents
= 500 cents
number of cents Josie will get back
500 - 260
240 cents or $2.40
So, Josie will get 240 cents back
Not 100% positive, but I think that it’s
13
10
9
16
15
11
14
12
I hope this helps
Hello :
the general term is :
an = a1+(n-1)×d
or : an = ap +(n-p)×d......d is common diffrence
let : n=10 and p= 4
a10 = a4 +(10-4)×d
64 = 22 + 6d
6d = 42
d= 7
conclusion :
a4 = 22
a3 = 22-7=15
a2=15-7=8
a1= 8-7=1
<span>the first five terms : 1 , 8 , 15 , 22</span>
Answer:
Step-by-step explanation:
(a - b)² = a² + 2ab + b²
Area of square frame =side²
= (2b - 1)²
= (2b)² - 2*2b * 1 + 1²
= 4b² - 4b + 1